Effective approaches to water distribution network rehabilitation: Fuzzy synthetic evaluation - M. Omer, Mazen; Abdelrahman, M. Farouk; Rahimi, A. Rahman; Noor Suraya, Romali (AIP Publishing, 2023)
It is crucial for countries to achieve sustainability; sustainable development is regarded as one of the goals for all nations. Non-revenue water (NRW) is one of the barriers that face water suitable development. To solve this issue and overcome the NRW barrier, this study aims to evaluate the effectiveness of water distribution network (WDN) rehabilitation approaches. To achieve this, 21 WDN rehabilitation approaches were identified from a systematic review of 327 articles. Also, a questionnaire survey was conducted to gather data from Malaysia and Egypt. Therefore, data gathered from 176 valid responses were analyzed using Cronbach, Descriptive, Normalization, and Factor analysis. In addition, Fuzzy synthetic evaluation (FSE) is employed to evaluate the effectiveness level of identified approaches. Besides, the result from factor analysis shows seven groups for WDN rehabilitation approaches. Out of the seven groups, FSE revealed that ‘Zoning network’ is the highest effect with an impact level of (4.23). This study provides a depth understanding of WDN rehabilitation approaches to conquer the barriers of water sustainability. It also serves as a guide to assists policymakers in putting in place measures to prevent or extirpate NRW. Overcoming NRW could help achieve water development and sustainability goals in developing countries